Media dalam kehidupan dan perkembangan kanak-kanak - Wan Abas, Wan Anita; Hamzah, Azizah (Department of Media Studies, Faculty of Arts & Social Sciences, University of Malaya, 2013)
This paper discusses the literature on the role of media in the lives and physical, behavioral, and cognitive development of children. The Bronfenbrenner Ecological Model is used as an approach for discussing this issue. According to literature, the relationship between children's use of and exposure to media, and their ecological contexts are determined by three important aspects, namely: poor diet; pro- and anti-social behavior; and academic achievement. In addition to a discussion of traditional and new electronic media, this paper pays special attention to how ecological context shapes television effects on child development. The author presents guidelines for parents who are concerned with the best way to manage media use among their children.